Design and Validity of Interactive Multimedia Based on Cognitive Conflict Using Adobe Animate CC on the Concept of Circular Motion - Suhadah, Olivia; Mufit, Fatni (Faculty of Science and Education, UIN Walisongo Semarang, 2023)
High school students' understanding of circular motion material is still low. One solution to this problem is to design interactive multimedia based on the cognitive conflict in the theory of circular motion to enhance the conceptual understanding of high school students. This study aims to determine the characteristics and validity of interactive multimedia based on cognitive conflict. The research follows the development research approach using the Plomp model. This study is limited to the preliminary study phase and the development phase, up to the validity test through expert review. The learning instruments include journal analysis sheets, teacher questionnaires, self-evaluation sheets, and expert review sheets. Data were analyzed using the percentage technique and the V-Aiken formula. The introductory study identified several issues in teaching circular motion, such as low understanding levels, teacher-centered physics instruction, lack of experimental activities, and a lack of interactive multimedia teaching materials. During the development stage, multimedia was designed with the following characteristics: the use of Adobe Animate CC 2019 application to support interactivity through students' smartphones. The multimedia was also structured according to the four learning model syntax based on cognitive conflict (CCBL model). The results of the self-evaluation test met the criteria for a very good rating, while the expert review test indicated a valid category. It can be concluded that the cognitive conflict-based interactive multimedia on circular motion material is valid and can proceed to the practical and effective testing stage.